Association between TyG-BMI and early-onset hypertension: evidence from NHANES - Wushuang Li; Chenliang Ge; Jianyong Zhou (Scientific Reports)
Abstract Early-onset hypertension (EHT) is a growing concern due to its long-term cardiovascular risks. This study investigated the association between the triglyceride glucose-body mass index (TyG-BMI) and EHT in a nationally representative US sample. EHT was defined as physician-reported hypertension diagnosed before age 40. We used weighted logistic regression models to assess the association between TyG-BMI and EHT, adjusting for potential confounders. Mediation analysis was conducted to examine the role of oxidative stress and inflammation markers in this association. We analyzed data from 5193 adults with age under 40 years from the National Health and Nutrition Examination Survey (NHANES) 2009–2018.Participants with EHT had significantly higher TyG-BMI compared to those without EHT (P < 0.001). In multivariable analysis, the highest quartile of Ty-BMI was independently associated with 6.47-fold increased odds of EHT (OR: 6.47, 95% CI: 4.35–9.61) compared to the lowest quartile. This association remained significant across subgroups stratified by gender, race, and smoking status. Gamma-glutamyl transferase (GGT) and uric acid were identified as potential mediators. Higher TyG-BMI is significantly associated with EHT. TyG-BMI may serve as a readily available clinical tool for early identification and management of individuals at increased risk for EHT, facilitating timely interventions to mitigate long-term cardiovascular risks.